The Complexities of the Mother's Role in Providing Early Childhood Learning Experiences for Children with Developmental Delays - Rosepti, Popi (Muslim Education Review, 2022)
The mothers’ role in bringing up children with developmental delays seems to be challenging. Problems when they decide to access occupational therapy to help their children’s development have been revealed. Therefore, this study aimed to explore the common complexities that mothers experience while taking their children to occupational therapy as a rehabilitation program to deal with developmental delays. As well, it also describes mothers’ personal efforts in tackling those complexities. Five semi-structured interviews were conducted with eight mothers and Colaizzi’s method was used to analyze the data as proposed by the phenomenological approach. The results reveal that mothers experience complexities when their children are diagnosed as having developmental delays. These include sadness and shock, panic and confusion, and guilt. Other difficulties include time management, cost demands, and support systems related to the therapy process. In tackling those complexities, mothers need to build their capacity for self-efficacy and self-empowerment as well as try to accept their children’s condition and to change habits as recommended by therapists. Not only describing the phenomenon, this study also analyzed some developmental screening tests applied in different countries to come up with new models of preventive actions in Indonesia.